Strategi Komunikasi Pemasaran Industri Kreatif Fotografi dalam memanfaatkan Media Digital (Analisis Pada Diary Photography Dalam Menghadapi Persaingan Industri) - Agil, Agil Tri Albari (Lentera Ilmu Madani, 2024)
ABSTRACT Digital marketing is very helpful to an attempt to introduce a product or goods sold in order to gain the advantage of having its own strategy used by Diary Photography to be able to continue to increase and compete with other photography entrepreneurs. The purpose of this research is to find out how strategies make use of Digital Media and its obstacles in the face of the competition of the creative industry (Wedding Photography) in the city of Palembang. This type of research is field research with a qualitative descriptive approach. Data collection techniques are observations, interviews, documentation and data analysis. The object of this research is Wendi, the owner of Diary Photography. This research uses Kotler's AIDA theory. The results of this research are Attention, Interest, Desire, Action Strategy This uses Diary Photography to generate consumer interest in seeing Diary photography in a different way on social media Instagram and Instagram Feature Selection is quite intelligent used to promote. Keywords : Photography, Digital, Media